Kesahan dan kebolehpercayaan modul I-Sc (Islamic Spiritual Counseling) ke atas pelajar bermasalah tingkah laku - Md Noor Saper,; Nurul Ain Mohd Daud,; Norazani Ahmad, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
The purpose of this study is to develop a counselling module based on Islamic perspective namely ‘Islamic Spiritual Counselling Module”’(i-SCM). This module was based on model of Tazkiyat al-Nafs by Imam Ghazali. Validity test was conducted based on assessments from various experts of psychology, counselling and religious fields. Reliability test was conducted on 46 secondary school students in one school. Results obtained showed that the overall reliability coefficient of this module was very high; Cronbach Alpha 0.927. Feedback from the respondents on the module was positive. This study could help expand further religion-related counseling module to assist counsellors in dealing with adolescents’ social problems.